Studies on Ottoman Social and Political History : Selected Articles and Essays - Karpat, Kemal H. (Social, Economic and Political Studies of the Middle East and Asia, 2002)
This book comprises a collection of articles and essays published in a variety of journals during the past decades, which seek to identify and analyze mainly the internal forces which transformed the Ottoman State into a variety of national states in the Balkans and the Middle East. Kemal H. Karpat studies the transformation of miri (state) lands into private property, the subsequent rise of a new propertied middle class in the countryside with its own stratum of intellectuals and notables as preparing the rise of a civil order which embraced or rejected as the situation demanded the old statist philosophy and the new bureaucracy. The book studies migration as a key factor which brought many Muslim ethnic groups into Anatolia that produced a social restructuring and new modern Ottoman-Islamic-Turkish culture that formed the ethno-cultural roots of Republican Turkey.